Особливості мотиваційного менеджменту на підприємствах харчової промисловості - Драган, Олена Іванівна; Болотіна, Ірина Миколаївна (My University, 2022)
В статті розглянуто аспекти мотиваційного менеджменту на підприємствах харчової промисловості. Визначено актуальність мотивації персоналу в сучасних умовах функціонування промислових підприємств на рівні промисловості. Проаналізовано особливості мотиваційного менеджменту на підприємствах харчової промисловості. Обумовлено, що використання широкого спектру методів мотивації суттєво покращує мотиваційний потенціал персоналу. Зокрема, в компанії «Кока Кола Беверіджиз Україна Лімітед», крім традиційних методів матеріального та нематеріального мотивування, співробітники можуть скористатися підтримкою під час переїзду, безоплатним розвезенням до території заводу та безкоштовно харчуватися в їдальні. Саме такі заходи суттєво заохочують до плідної праці та підвищують лояльність персоналу до компанії. Дослідження свідчить, що підприємства харчової промисловості активно використовують основні елементи мотиваційного менеджменту, і, це сприяє більш ефективній, продуктивній роботі працівників. The aspects of motivational management at food industry enterprises are discussed in the article. The relevance of personnel motivation in modern conditions of the functioning of industrial enterprises at the industrial level is determined. Nowadays there is a lack of scientific publications that would analyze motivational management specifically at food industry enterprises is investigated. The peculiarities of motivational management at food industry enterprises are analyzed. In particular, JSC “Obolon”, “Coca Cola Beverages Ukraine Limited” and JSC “Kyiv Confectionary Factory “Roshen” use a whole range of material and non-material methods of stimulation for effective motivational management. As a rule, motivation is based on two components – material (70%) and non-material (30%). Material motivation consists of three components: a system of basic salaries + bonus system + system of compensation payments. The remuneration of top managers depends on the competencies, the area of responsibility and the results of work within the limits of specific powers. The use of wide range of motivational methods significantly improves the motivational potential of personnel. For example, in Coca-Cola Beverages Ukraine Limited company, in addition to traditional methods of material and non-material motivation, employees can take advantage of support during relocation, free transportation to the factory premises, and free meals in the canteen. Such measures significantly encourage production work and increase staff loyalty to the company. Also, it is interesting to know the experience of JSC “Kyiv Roshen Confectionary Factory” in the application of workers’ punishments who committed violations of labour discipline, internal labour regulations and labour protection rules. They are either not charged a bonus, or it is reduced by a certain percentage, regardless of whether or not the employee is brought to disciplinary action, in certain amounts. Thus, the main elements of motivational management are actively used at food industry enterprises, which contributes to more efficient and productive work, the development of motivational potential and staff loyalty.
Keywords: кафедра економіки праці та менеджменту; мотиваційний менеджмент; мотивація; матеріальне та нематеріальне стимулювання; підприємства харчової промисловості; motivational management; motivation; material and non-material stimulation; food industry enterprises